STATUS GIZI BALITA DI POSYANDU DUSUN BELIK, KALURAHAN DEMANGREJO, KAPANEWON SENTOLO, KULON PROGO - Rokhayati; Mahardika Ratih Resti Andani; Este Latifahanun; Safirina Aulia Rahmi; Sarif Febriandi (Jurnal Ilmu Kesehatan Mulia Madani Yogyakarta, 2024)
Abstrack Background:. Nutrition plays an important role in the human life cycle. The period of infancy and toddlerhood is also called the window of opportunity, namely the golden period of growth and development. Nutrition is one of the factors that determines success in achieving optimal growth and development in infancy and toddlerhood. Toddlers in Indonesia experience double nutritional problems, on the one hand they are obese, but on the other hand they experience stunting, anemia, thinness, and even malnutrition. The results of the Indonesian Nutrition Status survey show that in Indonesia there are still 17% of underweight toddlers. Meanwhile in the Yogyakarta Special Region province there are 1.8% of toddlers with very underweight and 8.3% of toddlers with underweight in 2022. Efforts to improve the nutritional status of the community will make a real contribution to achieving national development goals, especially in terms of reducing the prevalence of malnutrition among children under five which will ultimately improve the quality of human resources. Posyandu is a Community Based Health Effort (UKBM) in basic health service activities, one of the activities of which is routine monthly weighing of toddlers to monitor the health condition of toddlers. Objective: To find out the description of the nutritional status of toddlers in the Posyandu for toddlers in Dusun Belik, Demangrejo Village, Sentolo District, Kulon Progo Regency, Yogyakarta. Methods: Type of quantitative descriptive research. Samples were taken using a total sampling technique of 28 toddlers aged 6 - 60 months. The research instrument used a posyandu registration book which contained the results of anthropometric examinations of toddlers. Data analysis used univariate analysis with percentages.Results: Characteristics of toddlers based on gender of toddlers, namely 53.58% boys and 46.42% girls. The nutritional status of toddlers based on body weight/age has a good nutritional status of 82.14%, based on height/weight has a normal nutritional status of 75% and based on body weight/height has a normal nutritional status of 85.72%. Conclusion: The nutritional status of children under five was mostly good (82.14%). Keyword: Nutritional status, toddlers, posyandu